PASIR VULKANIK SEBAGAI BAHAN STABILITAS CAMPURAN GENTING BETON (STUDI EXSPERIMEN GRADASI PASIR GUNUNG KELUD PADA RADIUS 200 KM DI KOTA CARUBAN) - Joko Setiono setiono; Agus suhardono; Johanes Asdhi Purwanto (Prokons: Jurnal Teknik Sipil, 2019)
Genting is a utility roof materials above the building that serves as a protective weather and channeling rain water that was on it down. Alternative yangb concrete tiles is done more efficiently without the combustion process. Kelud the ash sand fly bergradai to the distance, in other words the farther the distance of the small grain diameter at a given radius. The heat caused by the Volcanic magma, ash makes Kelud Sand has a high water absorption, but will have saturated and rejected, resulting in bledding. By mixing sand times as a species, then an increase hidroulis and mechanical properties of an ideal mix ratio. From the experiment results for the compressive strength of the mixture 2: 2: 1 is stronger ie max 108.00 kg /cm2, a mixture of 3: 2: 1 compression stress value obtained sbesar 64.00 kg /cm2 and the mixture of 4: 2: 1 obtained compressive stress value of 24.00 kg /cm2. As for the bending stress fracture to a mixture of 2: 2: 1 max values obtained at 33.5 kg / cm2and for a mixture of 3: 2: 1 max values obtained at 23.33 kg /cm2 while for mixture 3: 2: 1 obtained value max of 5.33 kg /cm2, and water absorption in the saturated surface dry condition for a mixture of 2: 2: 1 obtained 10.23%, water absorption in the saturated surface dry condition for a mixture of 3: 2: 1 obtained 11.82 %, water absorption on the condition of saturated surface dry to mix 4: 2: 1 obtained 12.81%,. Then for mains water tembur can be seen in the discussion section, but can be inferred to mix 2: 2: 1 is more dense because Crystal showed a copy with a little water and a relatively dry and to a mixture of 4: 2: 1 indicates a copy with softer water crystals and evenly with a small diameter, both assessed at the time of maximum concentration, while for the mixture 3: 2: 1 is more porous at the same time. Keywords: genting concrete, hydraulic properties, volcanic gradient, mixed ideal